1995
DOI: 10.1111/j.1471-0528.1995.tb09098.x
|View full text |Cite
|
Sign up to set email alerts
|

Does early growth delay occur in diabetic pregnancy?

Abstract: Objective To identify the date of ovulation in pregnant women with Type 1 diabetes in order to assess the validity of the concept of early growth delay. Design Identification of ovulation by measurement of urinary luteinising hormone and assessment of fetal growth using ultrasound scan. Setting Diabetic pre‐pregnancy and antenatal clinic in a teaching hospital. Subjects Twenty women with Type 1 diabetes who had attended a pre‐pregnancy clinic. Measures Urinary LH, by laboratory and kit methods, during concepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…These findings were based on examinations of crown–rump length 7–14 weeks after the LMP, compared with the expected length calculated from the LMP. Other small studies found no such growth delay, or explained an apparent delay with menstrual or ovulatory disturbances . Focus in these studies was partly on a possible prediction of excess malformation risk in fetuses with growth delay in early pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were based on examinations of crown–rump length 7–14 weeks after the LMP, compared with the expected length calculated from the LMP. Other small studies found no such growth delay, or explained an apparent delay with menstrual or ovulatory disturbances . Focus in these studies was partly on a possible prediction of excess malformation risk in fetuses with growth delay in early pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that the fetal growth (BPD) was within the normal range at around 20 weeks and there was evidence of accelerated growth of the BPD during the second trimester. However, recently Steel et al 18 suggested that early growth delay is probably an artifact of incorrectly estimated ovulation date. We found that fetuses in the less well-controlled group have comparable BPD values at 13-14 weeks to the well-controlled group.…”
Section: Discussionmentioning
confidence: 99%
“…In the first trimester of pregnancy in diabetic women we found that some fetuses were smaller by sonography than expected from the mothers' menstrual histories (Pedersen & Merlsted‐Pedersen 1981). Some groups have been unable to reproduce our finding, for which we use the term early growth delay, and suggest that it might be an artefact resulting from inaccurate estimation of ovulation (Steel et al 1995).…”
mentioning
confidence: 87%